State Due Process Hearing Systems Under the IDEA: An Update. (December 2019) - Connolly, Jennifer F.; Zirkel, Perry A.; Mayes, Thomas A.
As part of its structure of cooperative federalism, the Individuals With Disabilities Education Act delegates to the states implementation, within broad specifications, of administrative adjudication systems. In light of the centrality of these systems of dispute resolution and the limited research to date, policy makers and practitioners need more current information about the variations in the state hearing and review officer systems nationwide. Based on a survey of state special education directors, this article provides an updated snapshot of due process systems in the 50 states and the District of Columbia. Key findings include the following: (a) the increased predominance of one-tier, rather than two-tier, systems, (b) a similar continuation of the gradual shift toward full-time hearing officers who are attorneys, (c) a corresponding cumulative trend toward administrative law judge agencies, and (d) common problems concerning the length of hearings, the recruitment and selection of hearing officers, and their professional development, with the attendant responses in progress focused on additional training and revised procedures. Overall, in addition to the limitations of a relatively short and structured survey, the key contextual considerations included (a) the predominance of six states that account for the vast majority of the adjudicated hearings, (b) the wide variety among the remaining states, and (c) the interplay with the other indicators of dispute resolution activity, including filings, resolution sessions, and mediation.